Poor Birth Outcomes in Malaria in Pregnancy: Recent Insights Into Mechanisms and Prevention Approaches - Chua, Caroline L. L.; Hasang, Wina; Rogerson, Stephen J.; Teo, Andrew (Frontiers in Immunology, 2021)
Pregnant women in malaria-endemic regions are susceptible to malaria in pregnancy, which has adverse consequences on birth outcomes, including having small for gestational age and preterm babies. These babies are likely to have low birthweights, which predisposes to infant mortality and lifelong morbidities. During malaria in pregnancy, Plasmodium falciparum-infected erythrocytes express a unique variant surface antigen, VAR2CSA, that mediates sequestration in the placenta. This process may initiate a range of host responses that contribute to placental inflammation and dysregulated placental development, which affects placental vasculogenesis, angiogenesis and nutrient transport. Collectively, these result in the impairment of placental functions, affecting fetal development. In this review, we provide an overview of malaria in pregnancy and the different pathological pathways leading to malaria in pregnancy-associated low birthweight. We also discuss current prevention and management strategies for malaria in pregnancy, and some potential therapeutic interventions that may improve birth outcomes. Lastly, we outline some priorities for future research that could bring us one step closer to reducing this health burden.